The use and perceived value of telestration tools in elite football - Jones, D.; Rands, S.; Butterworth, A. D. (International Journal of Performance Analysis in Sport, 2020)
The proliferation of technology allowing performance analysis practices to become more efficient and effective has grown rapidly in recent years. One such tool that has become widespread amongst elite football clubs is the use of telestration software which allow annotations to be drawn over video footage to illustrate key tactical, technical, physiological or psychological facets in an interactive manner. The purpose of this study is to investigate the use and application of telestration tools in elite football. A descriptive research approach was employed, using detailed questionnaires to gain the views and perceptions of elite analysts, coaches and players. Findings confirm the widespread use of telestration tools in elite football with 93% of respondents stating that it is "essential-very important" to their practice. In particular, telestration is found to play an integral role in oppositional analysis, especially when introducing key tactical information in pre-match meetings. Numerous barriers associated with the use of telestration were also uncovered in this novel, contemporary research which may help set the foundations for further research into telestration tools in sports not limited to football.